DAYA ANTI S(NPLRY1OCOCCUS AUREUS DARI FERMENTASI DAUN BEBERAPA JENIS TUMBUHAN OBAT - Kasim, Erniwati; Yulinery, T.; Hardiningsih, R.; Triana, E.; Napitupulu, R.N.R. (JURNAL BIOLOGI INDONESIA, 2005)
ABSTRACTAnti Staphylococcus aureus of the Fermented Leaves of Several Medicinal Plants. Thisresearch tried to enhance the antimicrobial activity especially against Staphylococcus aureusby fermenting the leaves with Acetobacter-Saccharomyces. The result showed that thesuspension of the leaves of Psidium guajava, Hibiscus rosasinensis, Daucus carota, Morindacitrifolia, Pyrus malus, Apium graviolens and Piper betle could inhi bit the growth of S.aureus,wh i le Persea gratissima, Amaranthus caudatus and Nothopanax scutellaria did not.Keywords : Staphylococcus aureus, medicinal plants, antimicrobial